(untitled) (Research, Society and Development, 2021)
Evaluate the prenatal care offered to women attended in the Unified Health System of Paraná in order to contribute to the decision making of managers. This is a descriptive cross-sectional study with a quantitative approach, carried out with pregnant women who underwent prenatal care. in public health services of a health region in the state of Paraná, in 2018. Data were collected through electronic medical records and records in spreadsheets of local managers. The results showed that of the 89 pregnant women who underwent prenatal care, 84.3% were captured before 12 weeks, 55% were classified as habitual risk. Of the pregnant women with intermediate and high risk, 73.7% had access to the specialized outpatient care service. However, only 14.3% of pregnant women had a record of gestational age in all consultations, 34.8% record a uterine height after 12 weeks, 37.1% record a weight and 52.8% received the care plan performed by Health professionals. Despite the fact that most women are classified as habitual risk, 61.1% had cesarean section as the mode of delivery. It is concluded that prenatal care has been offered satisfactorily. However, it is necessary that managers provide assertive training to the professionals involved, for the proper implementation of the Care Model for Chronic Conditions aiming at positive outcomes of the pregnancy-puerperal period.